(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: Gall bladder perforation (GBP) is a relatively rare complication of acute cholecystitis which results in higher mortality and morbidity. Radiological imaging plays a crucial role in determining the diagnosis and treatment of these group of patients. Material and methods: Our study is an observational study done over a period of 1 year in Assam Medical College, where radiological modalities of CT and ultrasonography were used to study various types of non-traumatic Gall bladder perforation. Statistical analysis was done using MS excel software (2010). Results: In our study, males were more common. Type II perforation and size of defect of more than 10 mm were most commonly seen. Imaging with ultrasonography and CT scan help in earlier diagnosis of the acute event and helps in better management of the patient as with their use we can not only determine the location, size of perforation but we can also detect the development of its complications such as abscess or fistula formation. Conclusion: Site, size of perforation along with development of complications can be detected by using radiological modalities such as ultrasonography and CT.